Does Social Presence on Social Commerce Platform Attract Buying Intention of Indonesian Local Food? - Ratni Prima Lita; Meuthia Meuthia; Devi Yulia Rahmi; M. Fajar Syafrida (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
Studying social commerce and consumer behavior in Indonesia is crucial due to the country's rapid digital transformation and unique cultural landscape. This study aims to investigate the effects of social commerce on consumer trust and buying intentions in Indonesia’s local food sector. This study uses a quantitative approach through hypothesis testing. Data was collected using questionnaires and purposive sampling techniques. A survey of 240 respondents was conducted, and data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). Results indicated that social commerce significantly influences trust in sellers and buying intention, while social support was not significantly affected. Social support and trust significantly influence purchase intention. However, the effect of social commerce on social support and trust in sellers through social presence moderation is not proven. This study highlights the role of social commerce in building consumer trust, though its effects on social support remain inconclusive. This research is interesting for developing social commerce to attract buyers' interest in local Indonesian food